GGE biplot analysis of Line by tester for seed yield and its attributes in sunflower - M A Ahmed; Mohamed Ali Abdelsatar; M A Attia; A A Abeer (RUDN Journal of Agronomy and Animal Industries, 2019)
Nine genetically diverse sunflower promising lines in their economic trait were crossed using line by tester mating design in 2018 spring season, to estimate per se performance, combining ability, heterosis, gene action and heritability for earliness, yield and its attributes traits. The parents involved four sunflower CMS lines namely L1 (A3), L2 (A5), L3 (A9) and L4 (A13) (called hereafter “Lines” (as female parents) and five sunflower genotypes T1 (RF9), T2 (RF10), T3 (RF11), T4 (RF14) and T5 (RF1) as male parents (called hereafter “Tester”). In 2018 and 2019 summer season, the nine parents along with their 20 F1s seeds were evaluated at Shandaweel Agricultural Research Station, ARC, Sohag Governorate, Egypt using a randomized complete blocks design with three replications. Mean squares due to parents (P), crosses (C), CMS lines (L), RF testers (T), P vs C and L x T were significant for all studied traits. A larger magnitude of non-additive gene action than additive was revealed by greater ratios (GCA/ SCA) than unity for all studied traits (except for days to 50% flowering). A5 and A13 of CMS lines and RF11 and RF14 of RF lines proved to be the best general combiners for seed weight plant-1 and one or more of its attributes traits. Moreover, the best cross combinations A13 x RF11, A13 x RF1 and A5 x RF9 performed better than other developed hybrids in view of seed weight plant-1 and one or more of its attributes, hence these F1 hybrids could further be used on commercial exploitation.